A Simulation Study on the Effect of Fluctuation of Water Level on the Stability of Reinforced Soil Wall - Tay, Yong Chyi; Felix Ling Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2023)
Sea level rise has induced the soil erosion and the effects of coastal lines contributes to water pollution, sedimentation in streams and rivers and can eventually lead to flooding. Therefore, bank protection structure is required with the aim to resist the effect of water fluctuation due to daily tidal cycle and ensure the stability of river bank. This study is aimed to evaluate the effectiveness of using Reinforced Soil wall as shoreline protection structure. A numerical simulation with combination of seepage analysis and slope stability analysis was carried out by using PLAXIS LE to study the effect of water table fluctuation on the stability of reinforced soil wall. Case study of failed levee at Phase 3 of Kerian River Flood Mitigation Project was taken as case study and reinforced soil wall with geotextile was proposed to improve the stability of slope. The results of numerical simulation have proven that the geotextile reinforced soil wall is able to treat the failed slope and the use of reinforced soil wall as retaining structure is able to meet the JKR’s requirement.